2011
DOI: 10.5187/jast.2011.53.2.161
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Methane Production in Korean Native Cattle (Hanwoo) Fed Different Grain Sources

Abstract: Methane production during anaerobic fermentation in the rumen represents an energy loss to the host animal and induces emissions of greenhouse gases in the environment. Our study focused on comparison in methane production from growing Korean native steers fed different grain sources. Six Hanwoo steers (BW = 180.6 ± 3.1 kg) were fed, on a DM basis (TDN 2.80 kg), 40% timothy and 60% barley concentrate (Barley) or corn concentrate (Corn), respectively, based on the Korean Feeding Standards. Each period lasted 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…These were much higher than the default values in the IPCC Tier 2 and the values previously measured in Hanwoo steers. A study measuring CH 4 emissions of growing Hanwoo steers using a hood-type chamber system, reported that MCF of growing Hanwoo steers was 5.5 and 6.5 % with corn- and barley-based diets, respectively (Seol et al 2011 ). The same group also showed that the MCF of Hanwoo steers in feedlots was 5 and 4 % with corn- and barley-based diets, respectively (Seol et al 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…These were much higher than the default values in the IPCC Tier 2 and the values previously measured in Hanwoo steers. A study measuring CH 4 emissions of growing Hanwoo steers using a hood-type chamber system, reported that MCF of growing Hanwoo steers was 5.5 and 6.5 % with corn- and barley-based diets, respectively (Seol et al 2011 ). The same group also showed that the MCF of Hanwoo steers in feedlots was 5 and 4 % with corn- and barley-based diets, respectively (Seol et al 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…The full database of the individual observations used in the current study is described in the Supplementary Information (Table S1). These papers and reports were chosen, because they reported experiments involving growing steers (n = 36) [10][11][12], fattening steers (n = 54) [13], growing heifers (n = 20) [12] and breeding cows (n = 31) [14] in which direct measurements of faecal, urinary and methane losses were made with an indirect respiratory calorimetry chamber [10,14] and head hood chamber system [11][12][13] across a wide range of diet qualities. Specifically, the selected papers represented a wide range of dietary DE (1.70 to 3.51 Mcal/kg DM), ME (1.44 to 3.21 Mcal/kg DM), crude protein (CP, 5.61% to 17.05%), ether extract (EE, 1.05% to 3.28%), neutral detergent fibre (NDF, 30.36% to 72.0%) and acid detergent fibre (ADF, 16.20% to 44.81%) concentrations (DM basis).…”
Section: Database Source and Descriptionmentioning
confidence: 99%